Pengaruh Risiko Bisnis, Likuiditas, Struktur Aset, Profitabilitas, Ukuran Perusahaan Terhadap Kebijakan Hutang Pada Perusahaan Food and Beverage Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Wisnugroho Wisnugroho; Sri Rahayu; Eka Handriani (Journal Of Business, Finance, and Economics (JBFE), 2023)
This research was conducted to determine the effect of Business Risk, Liquidity, Asset Structure, Profitability, and Company Size on Debt Policy. The sample used in this study amounted to 24 companies that met criteria, so that the total sample used in this study was 120 observational data. The hypothesis used is the associative hypothesis. The research data source is a secondary data source. The data analysis tool used is SEM-PLS 4.0 for Windows. The result showed that (1) Business Risk has an effect on Debt Policy, (2) Liquidity has an effect on Debt policy, (3) Asset Structure has no significant effect on Debt Policy, (4) Profitability has an effect on Debt Policy, (5) Firm Size has an effect on Debt Policy, (6) Business Risk, liquidity, Asset Structure, Profitability, and Firm Size simultaneously effect Debt policy.